Answer:
F
Step-by-step explanation:
Answer:
42 quarts
Step-by-step explanation:
<span>4x</span>² <span>+ 13x + 3=
4x</span>² + 12x + x + 3 =
4x(x+3) + (x+3) =
(4x+1)(x+3)
Answer:
f(x) = + cosx or - cosx
Step-by-step explanation:
(2+tan^2x/sec^2x) -1 =(f(x))^2
=(( 1 + sec^2x)/sec^2x) -1
= 1 / sec^2x + 1 - 1
= 1 / sec^2x
= cos^2x
(f(x))^2 = cos^2x
f(x) = + cosx or - cosx
3^2 + 4^2 = 5^2
9 + 16 = 25
25 = 25
5^2 + 12^2 = 13^2
25 + 144 = 169
169 = 169
9^2 + 12^2 = 15^2
81 + 144 = 225
225 = 225
<span>a^2 + b^2 is = to c^2</span>